2019
DOI: 10.2147/ott.s192641
|View full text |Cite
|
Sign up to set email alerts
|

<p>lncRNA small nucleolar RNA host gene 20 predicts poor prognosis in glioma and promotes cell proliferation by silencing P21</p>

Abstract: BackgroundIn multiple cancers, long non-coding RNA small nucleolar RNA host gene 20 (lncRNA SNHG20) is generally dysregulated. In the present study, both the biological role and clinicopathological value of lncRNA SNHG20 in glioma are explored.MethodsReal-time PCR was employed to determine lncRNA SNHG20 expression in glioma patients. The prognostic role of expression of lncRNA SNHG20 was evaluated in a retrospective cohort study. In addition, the association between lncRNA SNHG20 expression and the clinicopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Meanwhile, 8 studies with 828 patients were included to evaluate the link of SNHG20 and histological grade. Heterogeneity difference was not observed among the studies ( I 2 = 0.0%, P = .572), [ 9 11 , 19 , 21 , 23 25 ] and the pooled OR was 2.11 (95% CI: 1.55–2.87, P < .001), indicating that high SNHG20 expression predicted higher histological grade (Fig. 2 b).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Meanwhile, 8 studies with 828 patients were included to evaluate the link of SNHG20 and histological grade. Heterogeneity difference was not observed among the studies ( I 2 = 0.0%, P = .572), [ 9 11 , 19 , 21 , 23 25 ] and the pooled OR was 2.11 (95% CI: 1.55–2.87, P < .001), indicating that high SNHG20 expression predicted higher histological grade (Fig. 2 b).…”
Section: Resultsmentioning
confidence: 94%
“…[ 22 ] Furthermore, increasing researches suggested that SNHG20 participated in the tumorigenesis via EMT signaling pathway and p21 signaling pathway. [ 17 , 28 , 29 ]…”
Section: Discussionmentioning
confidence: 99%
“…In ovarian cancer, SNHG20 can activate WNT/β-catenin signaling pathway, which promotes cell proliferation (190). SNHG20 supports glioma cell survival by sponging miR-4486 and up-regulating MDM2-p53 pathway (191), and silencing p21 (192). This lncRNA is also involved in vasculogenic mimicry, a process of pseudo-vascular formation in highly aggressive cancers, via enhancement of ZRANB2/SNHG20/FOX1 axis (193).…”
Section: Small Nucleolar Rna Host Gene 20 (Snhg20)mentioning
confidence: 99%
“…These studies containing 1187 cancer patients had an accrual period between 2016 and 2019 and sample sizes varying from 32 to 144 (mean, 79). Each and every research study was performed in China; two studies referred to hepatocellular carcinoma [8,23], two studies involved osteosarcoma [10,24], two studies touched upon glioma [11,25], and the remaining nine studies related to colorectal cancer [12], gastric cancer [13], lung cancer [14], cervical cancer [15], esophageal carcinoma [16], oral carcinoma [17], nasopharyngeal carcinoma [18], ovarian cancer [19], and laryngeal carcinoma [20]. The whole subjects registered were separated into high and low SNHG20 group on the basis of the SNHG20 measurement results.…”
Section: Data Selection and Characteristicsmentioning
confidence: 99%
“…Initially, SNHG20 was discovered in hepatocellular carcinoma (HCC) and has been proved to function as an oncogene in HCC [8]. Subsequently, a growing body of research has identified that aberrant SNHG20 expression definitely interacted with prognostic outcomes and clinicopathological characteristics in patients with many kinds of malignancies, including bladder cancer [9], osteosarcoma [10], glioma [11], colorectal cancer [12], gastric cancer [13], lung cancer [14], cervical cancer [15], esophageal carcinoma [16], oral carcinoma [17], nasopharyngeal carcinoma [18], ovarian cancer [19], and laryngeal carcinoma [20]. Consistently, overexpression of SNHG20 could promote cell-cycle, proliferation, invasion, and migration of tumor cells via different mechanisms, while up-regulated SNHG20 is an unfavorable prognostic factor [7].…”
Section: Introductionmentioning
confidence: 99%